Telaah Kritis Pemikiran Ekonomi Islam Terhadap Mekanisme Pasar Dalam Konteks Ekonomi Islam Kekinian - Arif Wahyudi (EKSYAR : Jurnal Ekonomi Syari'ah & Bisnis Islam, 2014)
This article was aimed to explain the nature of market mechanism in Islamic economic thought as well as its practice in current days. Historical dan philosophical approach were used in the analysis to oversee Islamic basic teaching on market and to explore ideas and insights of muslim scholars regarding the subject. The article concluded that within Islamic framework, market mechanism has been regarded as important part of economic activities so that its existence has been main concern of many scholars. Market mechanism that protect people of the right and just price has also been considered as important and neccesary for better life. This then implied the need to keep market mechanism work which was part of government duties.